Additive Linking in Second Language Discourse: Lexical, Syntactic and Discourse Organizational Choices in Intermediate and Advanced Learners of L2 German with L1 French - Audrey Bonvin; Christine Dimroth (Discours)
This paper reports results from a study on the acquisition of additive scope particles as a means to enhance discourse coherence by French learners of German as a second language.    It addresses the questions of which additive devices intermediate and advanced learners produce; which possibilities of syntactic integration in relation to the added constituent they use; and whether they choose target-like information units in order to establish additive relations across utterances. Oral production data from an elicited discourse production study reveal that the form of the additive expressions among advanced learners nearly always corresponds to the pattern preferred in the target language without, however, tapping its full potential. Rather, learners overuse options that are formally but not functionally similar in both languages.    This uniform behavior at the utterance level does not go hand in hand with target-like preferences for discourse organization. Native speakers of German tend to construe stretches of discourse as an answer to an implicit YES/NO question. They focus on the occurrence of events and use the assertion component to establish links and comparisons across utterances. Native speakers of French, on the other hand, prefer to construe utterances as answering implicit Wh-questions, thereby focusing discourse entities and establishing contrasts between them.    Based on their first language’s entity-based utterance organization, even advanced second language learners of German are shown to use a hybrid system, establishing mainly entity-based and only a few assertion-based discourse relations.